Patient and service user engagement in research: a systematic review and synthesized framework. (3rd June 2013) - Shippee, Nathan D.; Domecq Garces, Juan Pablo; Prutsky Lopez, Gabriela J.; Wang, Zhen; Elraiyah, Tarig A.; Nabhan, Mohammed; Brito, Juan P.; Boehmer, Kasey; Hasan, Rim; Firwana, Belal; Erwin, Patricia J.; Montori, Victor M.; et al.
Abstract: Background: There is growing attention towards increasing patient and service user engagement (PSUE) in biomedical and health services research. Existing variations in language and design inhibit reporting and indexing, which are crucial to comparative effectiveness in determining best practices. Objective: This paper utilizes a systematic review and environmental scan to derive an evidence‐based framework for PSUE. Design: A metanarrative systematic review and environmental scan/manual search using scientific databases and other search engines, along with feedback from a patient advisory group (PAG). Eligible sources: English‐language studies, commentaries, grey literature and other sources (including systematic and non‐systematic reviews) pertaining to patient and public involvement in biomedical and health services research. Data extracted: Study description (e.g. participant demographics, research setting) and design, if applicable; frameworks, conceptualizations or planning schemes for PSUE‐related endeavours; and methods for PSUE initiation and gathering patients'/service users' input or contributions. Results: Overall, 202 sources were included and met eligibility criteria; 41 of these presented some framework or conceptualization of PSUE. Sources were synthesized into a two‐part framework for PSUE: (i) integral PSUE components include patient and service user initiation, reciprocal relationships, colearning and re‐assessment and feedback, (ii) sources describe PSUE at several research stages, within three larger phases: preparatory, execution and translational. Discussion and Conclusions: Efforts at developing a solid evidence base on PSUE are limited by the non‐standard and non‐empirical nature of much of the literature. Our proposed two‐part framework provides a standard structure and language for reporting and indexing to support comparative effectiveness and optimize PSUE.